A renal adenocarcinoma in a corn snake (Pantherophis guttatus) resembling human collecting duct carcinoma. (September 2016) - Kao, Chi-Fei; Chen, Jiun-Liang; Tsao, Wen-Tien; Lee, An-Hsing; Liu, Chen-Hsuan; Wang, Fun-In
A 5-year-old male captive corn snake ( Pantherophis guttatus ) with caudal coelomic swelling was admitted for surgical treatment. Laparotomy revealed a 5 × 4 × 2.5 cm, firm, expansile, irregularly shaped mass arising from the middle portion of the right kidney with a mild lobulated pattern and mottled white-to-tan. Microscopically, the mass was composed of numerous bizarre angulated tubules of polygonal neoplastic cells separated by a scirrhous stroma with remarkable heterophilic infiltrates. The neoplastic cells were nonciliated and mucin secreting, with abundant brightly eosinophilic cytoplasm. There were marked cellular and nuclear atypia, frequent cell individualization, and stromal invasion, indicative of malignant behavior, which was confirmed by metastasis to the left kidney 1.5 months postoperatively. Both neoplastic epithelial cells and mesenchymal cells contributing to the scirrhous stroma had variable immunopositivity for pan-cytokeratin. The neoplasm was considered a renal adenocarcinoma resembling human collecting duct carcinoma.